Life design and career counseling: contributions to social justice - Duarte, Maria (2018)
The chapter begins with the presentation of LDC framework. In the second section, considerations are given on LDC possibilities for enhancing decent work and social justice. From this perspective of social exclusion, designated social integrationist, participation in paid work is viewed as the key to social inclusion (Watts, 2001). At the end of this section the relevance of contextual factors in career development of disadvantaged populations is referred to highlight the importance of these interventions not be exclusively focused on inter- and intrapersonal career development factors, but also take into consideration social action at the institutional, community, public policy and international/global levels (Cook, 2017). In the next section, the process of balancing the focus on the self-determination of the individual with a focus on a transformation of contextual factors that reinforce the disadvantaged position (Blustein, et al., 2005; Prilleltensky, 1997) is illustrated by presenting an intervention in which LDC was integrated into supported employment approach. Our proposal focuses exclusively on collaborative activities at the individual, institutional and communal level, with these being the tiers which the counselor can more easily influence as part of their more routine interaction with disadvantaged populations in general. The chapter concludes with an overview of the subject and a reference on LDC limitations for the intervention with disadvantaged populations in general.